1999
DOI: 10.1002/(sici)1097-4628(19991017)74:3<728::aid-app27>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Influence of branching on the properties of poly(ethylene terephthalate) fibers

Abstract: A series of branched poly(ethylene terephthalate) samples was prepared by employing 0.07-0.42 mol % trimethylolpropane (TMP) for melt polycondensation. These polymers were characterized with respect to molar mass, intrinsic viscosity, and melt viscosity. Spinning into fibers took place at spinning speeds ranging from 2500 to 4500 m/min. The molecular orientation of the fibers as measured by birefringence and polarized fluorescence decreases with growing amounts of TMP, as does crystallinity. Thus with slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 6 publications
4
15
0
Order By: Relevance
“…Using a fixed level of PER and varying levels of benzyl alcohol as an end-capper they concluded that the fall in their zero shear viscosity values was due to branching. Other authors [13][14][15][16][17]27,28] also found zero shear viscosity for branched species to be lower than that of linear PET analogues. In contrast, a reactive extrusion process of PET with polyanhydride and polyepoxide modifiers gave rise to increased viscosities, [18][19][20][21][22] attributed to a combination of long chain branching, molecular weight increase and broadening of the molecular weight distribution.…”
Section: Rheological Characterization Using Oscillatory Flow Measuremsupporting
confidence: 89%
See 1 more Smart Citation
“…Using a fixed level of PER and varying levels of benzyl alcohol as an end-capper they concluded that the fall in their zero shear viscosity values was due to branching. Other authors [13][14][15][16][17]27,28] also found zero shear viscosity for branched species to be lower than that of linear PET analogues. In contrast, a reactive extrusion process of PET with polyanhydride and polyepoxide modifiers gave rise to increased viscosities, [18][19][20][21][22] attributed to a combination of long chain branching, molecular weight increase and broadening of the molecular weight distribution.…”
Section: Rheological Characterization Using Oscillatory Flow Measuremsupporting
confidence: 89%
“…Indeed a certain number of papers have been published on the improvement of the rheological properties of PET prepared in the presence of a variety of branching agents. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] A description of the synthesis of a dozen of branched polyesters via different tri-and tetrafunctional comonomers is given in the review paper of McKee et al [9] Modification of polyesters by introducing long chain branching has received significant attention as an efficient method to enhance melt strength and melt viscosity. Randomly branched polyesters are often prepared by stepgrowth polymerization in the presence of multifunctional comonomers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BPET has also found its important application in high speed spinning fiber formation. Hess et al found less oriented structure developed in BPET fibers than in LPET fibers under the same spinning speed, which would impeded stress induced crystallization and reduced the unstabilities of high-speed spinning [7]. Different methods have been explored to prepare BPETs.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion had to be lowered to avoid crosslinking because of the higher comonomer content. Hess et al 8 reported that branched PET fibres containing 0.07–0.42 mol% of trimethylolpropane were produced at higher spinning speed than linear PET.…”
Section: Introductionmentioning
confidence: 99%